Diagnostic Approach for Thyroid Nodules - Dante Saksono Harbuwono; Pradana Soewondo; Em Yunir; Suharko Soebardi; Budiman Darmowidjojo; Dyah Purnamasari; Tri Juli Edi Tarigan; Wismandari Wisnu; Dicky Levenus Tahapary; Farid Kurniawan; Erwin Danil Yulian; Lisnawati Lisnawati; et al. (Interna Publishing, 2019)
Thyroid nodule is a health problem which commonly found in daily practice, therefore clinical guidance is needed. This guideline was compiled by a multidisciplinary team and expected to be a guideline in diagnosing thyroid nodules on daily clinical practice.